Examining mortality risk and rate of ageing among Polish Olympic athletes: a survival follow-up from 1924 to 2012. Issue 4 (18th April 2016) - Lin, Yuhui; Gajewski, Antoni; Poznańska, Anna
Abstract : Objectives: Population-based studies have shown that an active lifestyle reduces mortality risk . Therefore, it has been a longstanding belief that individuals who engage in frequent exercise will experience a slower rate of ageing. It is uncertain whether this widely-accepted assumption holds for intense wear-and-tear. Here, using the 88 years survival follow-up data of Polish Olympic athletes, we report for the first time on whether frequent exercise alters the rate of ageing. Design: Longitudinal survival data of male elite Polish athletes who participated in the Olympic Games from year 1924 to 2010 were used. Deaths occurring before the end of World War II were excluded for reliable estimates. Setting and participants: Recruited male elite athletes N=1273 were preassigned to two categorical birth cohorts—Cohort I 1890–1919; Cohort II 1920–1959—and a parametric frailty survival analysis was conducted. An event-history analysis was also conducted to adjust for medical improvements from year 1920 onwards: Cohort II. Results: Our findings suggest (1) in Cohort I, for every threefold reduction in mortality risk, the rate of ageing decelerates by 1%; (2) socioeconomic transitions and interventions contribute to a reduction in mortality risk of 29% for the general population and 50% for Olympic athletes; (3) an optimum benefit gained for reducing the rate of ageing from competitive sports (Cohort I 0.086 (95% CI 0.047 to 0.157) and Cohort II 0.085 (95% CI 0.050 to 0.144)). Conclusions: This study further suggests that intensive physical training during youth should be considered as a factor to improve ageing and mortality risk parameters.